COMMENT TO: “VOLCANIC ACTIVITY FROM THE NEOGENE TO THE PRESENT EVOLUTION OF THE WESTERN MEDITERRANEAN AREA. A REVIEW” BY M. LUSTRINO - Elter, Franco Marco (Ofioliti, 2001)
In the Discussion and Conclusions of the paper “Volcanic activity from Neogene to the present evolution of the Western Mediterranean sea. A review” (Ofioliti, 25 (2): 87- 101), by Michele Lustrino, mainly deals with the Neogene to present volcanic activity and it presents a “continuous” model from Hercynian time to present: the paper, particularly because it wants to be a review, must take in better and more complete consideration the present-day knowledge on bibliography, data and interpretations, about the Hercynian, Late Hercynian and post-Hercynian geodynamic evolution in Western and Southern Europe. The Discussion and Conclusions chapter reports, in particular, some considerations about the Hercynian and post- Hercynian geodynamic evolution that do not take in consideration present interpretations developed by recent geological, structural and petrological-geochemical investigations carried out by several authors. The presentation of some main topics of this evolution is particularly inadequate for an up-to-date review published on an international bulletin.